Prospects for the development of laser technologies - Savchenko, O. M. (ХНУРЕ, 2022)
A characteristic feature of modernity is the extremely rapid development of technology in all areas of human activity. The development of production causes the ever-increasing introduction of high-tech technologies, which include laser processing of materials.
Keywords: laser processing; materials